Knowledge and Attitudes of Future Healthcare Professionals Toward Rare Diseases - Domaradzki, Jan; Walkowiak, Dariusz (Frontiers in Genetics, 2021)
Caring for patients suffering from a rare disease (RD) requires the special and combined efforts of different healthcare professionals, including nurses, physiotherapists and physicians. Nevertheless, Poland still lacks a national plan for RDs and the undergraduate and postgraduate education of future healthcare professionals on RDs is also inadequate. Thus, the aim of this study was to assess the awareness of RDs among nursing, physiotherapy and medical students in Poland. It shows that although 98% of respondents had heard of the term “rare disease,” most students had problems in defining the most common causes of RDs and their prevalence. Students also lacked basic knowledge about the healthcare system for RD patients in the country. While over 95% of future nurses, physiotherapists and physicians assessed their knowledge about RDs as insufficient or very poor, almost 92% of medical students, and 84% of physiotherapy and nursing students, did not feel prepared for caring for RD patients. Furthermore, although the vast majority of respondents declared eagerness to broaden their knowledge on RDs, only 45% of medical students, 76% of nursing students and 88% of physiotherapy students believed that RDs should be included into the medical curricula. Simultaneously, for most students the Internet was the prime source of information on RDs. It is concluded that as caring for RD patients requires a multidisciplinary approach, by identifying the gap in the education of future nurses, physiotherapists and physicians this study shows that there is an urgent need of better education about RDs among future healthcare professionals.